Critique of the Hadith "Were I to command one to prostrate to another, it would be …." - Sultan Saad Alsaif (Journal of Islamic Studies, 2015)
This research investigates the Hadith ("Were I to command one to prostrate to another, it would be wife to husband.",. This Hadith's tracks or sources and evidences are numerous, and they need to be carefully examined, especially as the Hadith has been a subject of talk by non-specialists, due to ignorance, arrogance, whims, or distortion purposes. The controversy has attracted arguments for and against the Hadith; some even claimed it to be inconsistent with the Qur'an despite its hypothetical condition. This necessitates Hadith specialist inquiry into it so that the truth of the matter can be available to all, and distortion attempts can be thwarted. The research aims to: gather and document all versions of the Hadith; to establish the reliability of the Hadith; and to refute whimsical allegations that are entertained by parties ignorant of related religious teachings. Methodologically, the research applies an inductive-deductive approach. It ends with thirtythree conclusions related to the Hadith chains of narrators, ranking, implications and linguistic analysis.